HEART ELECTRICAL AXIS α ANGLE VALUES DISTRIBUTION IN PATIENTS, UNDERGOING PERMANENT PACEMAKER IMPLANTATION - Voronenko, O. S.; Brynza, M. S.; Volkov, D. E.; Lopin, D. O.; Martynenko, O. V.; Yabluchansky, M .I. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 2016)
52 patients (24 male and 28 female) aged 71 ± 8 years, underwent permanent pacemaker implantation were included in the study. Analysis of heart electrical axis (HEA) α angle values distribution was carried out in three dimensions in patience before and after pacemaker (PM) implantation. The data processed in Microsoft Excel with calculation of the average and it’s standard deviation. Significance of differences in data before and after PM implantation was assessed using Friedman ANOVA test and Kendall concordance coefficient. It was found, that α angle values distribution in patients with implanted PM is transformed from a unimodal to bimodal on the permanent cardiac pacing background. It’s assumed, that α angle changes resulting due to right ventricular electrode positioning options during PM implantation. Clarification of the nature of this change requires a special study.